High pressure processing of meat: effects on ultrastructure and protein digestibility. Issue 5 (4th May 2016) - Kaur, Lovedeep; Astruc, Thierry; Vénien, Annie; Loison, Olivier; Cui, Jian; Irastorza, Marion; Boland, Mike
Abstract : The effects of high pressure processing (HPP, at 175 and 600 MPa) on the ultrastructure and in vitro protein digestion of bovine longissimus dorsi muscle meat were studied. Abstract : The effects of high pressure processing (HPP, at 175 and 600 MPa) on the ultrastructure and in vitro protein digestion of bovine longissimus dorsi muscle meat were studied. HPP caused a significant change in the visual appearance and texture of the meat subjected to HPP at 600 MPa so that it appeared similar to cooked meat, unlike the meat subjected to HPP at 175 MPa that showed no significant visible change in the colour and texture compared to the raw meat. The muscles were subjected to digestion under simulated gastric conditions for 1 h and then under simulated small-intestinal conditions for a further 2 h. The digests were analysed using gel electrophoresis (SDS-PAGE) and ninhydrin assay for amino N. The effect of the acid conditions of the stomach alone was also investigated. Reduced SDS-PAGE results showed that pepsin-digested (60 min) HPP meats showed fewer proteins or peptides of high molecular weight than the pepsin-digested untreated meat, suggesting more breakdown of the parent proteins in HPP-treated meats. This effect was more pronounced in the muscles treated at 600 MPa. These results are in accordance with microscopy results, which showed greater changes in the myofibrillar structure after simulated gastric digestion of the sample processed at 600 MPa than at 175 MPa. Transmission electron microscopy also showed the presence of protein aggregates in the former sample, resulting probably from protein denaturation of sarcoplasmic proteins, in the subcellular space and between myofibrils; along with cell contraction (similar to that caused by heating) in the former.